Political values of local politicians representing non-profit organisations in Central Europe - Oto Potluka; Marybel Perez (University of Basel, Center for Philanthropy Studies (CEPS), 2017)
Local politicians in Central Europe are actively participating in civil society organizations (NGOs). The socialization of politicians into different roles would affect their political preferences and, therefore, policy outcomes. Thus, we study whether the political values of NGO leaders are aligned differently from those of political party peers who are not engaged in NGOs. We draw our analysis on survey data of 355 local candidates from three large cities: Prague, Bratislava, and Budapest. We analyse the political preferences of local political leaders in the context of the official political preferences of their parties. We also compare the perceptions of elected politicians with those of non-elected politicians, and subsequently analyse the effect of engagement in civil society activity. The results suggest that the local politicians are oriented towards local community values and are less likely to account for the official positions of their political parties. The only factor relating to a candidate's likelihood of election is the presence of a candidate's party in the national parliament.
Keywords: 330